Bacterial community responses to planktonic and terrestrial substrates in coastal northern Baltic Sea - Zhao, Li; Brugel, Sonia; Ramasamy, Kesava Priyan; Andersson, Agneta (Frontiers in Marine Science, 2023)
Bacteria are major consumers of dissolved organic matter (DOM) in aquatic systems. In coastal zones, bacteria are exposed to a variety of DOM types originating from land and open sea. Climate change is expected to cause increased inflows of freshwater to the northern coastal zones, which may lead either to eutrophication or to increased inputs of refractory terrestrial compounds. The compositional and functional response of bacterial communities to such changes is not well understood. We performed a 2-day microcosm experiment in two bays in the coastal northern Baltic Sea, where we added plankton extract to simulate eutrophication and soil extract to simulate increased inputs of refractory terrestrial compounds. Our results showed that the bacterial communities responded differently to the two types of food substrates but responded in a similar compositional and functional way in both bays. Plankton extract addition induced a change of bacterial community composition, while no significant changes occurred in soil extract treatments. Gammaproteobacteria were promoted by plankton extract, while Alphaproteobacteria dominated in soil extract addition and in the non-amended controls. Carbohydrate metabolism genes, such as aminoglycan and chitin degradation, were enriched by plankton extract, but not soil extract. In conclusion, the coastal bacterial communities rapidly responded to highly bioavailable substrates, while terrestrial matter had minor influence and degraded slowly. Thus, in the northern Baltic Sea, if climate change leads to eutrophication, large changes of the bacterial community composition and function can be expected, while if climate change leads to increased inflow of refractory terrestrial organic matter the bacterial communities will not show fast compositional and functional changes. Degradation of terrestrial organic matter may instead occur over longer periods of time, e.g. years. These findings help to better understand the ability of bacterial communities to utilize different carbon sources and their role in the ecosystem.